Evaluation and identification of morphological characters suitable for delimitation of Taraxacum species distributed in northeastern China. Issue 9 (22nd April 2022) - Jie, Wu; Qun, Liu; Cheng, Haitao; Ning, Wei; Cao, Wei
Abstract: Taraxacum germplasm resources in northeastern China are not current and do not accurately reflect the actual distribution of the species. The objective of this study was to investigate the morphological traits of Taraxacum species distributed in northeastern China and identify those that will facilitate their classification in this region. Leaf, flower, and achene characteristics of 18 species were used for morphological classification. Scanning electron microscopy (SEM) was used to examine pollen morphology. Internal transcribed spacer (ITS) sequences were analyzed to determine sequence differences among the species and their utility in delimitation. Taxa were classified into groups based on their morphology. The ITS sequence analysis supported the taxon classification, but the genetic distances among the taxa did not reflect morphological differences. Phylogenetic analysis was used to divide the 18 species into three groups. Group I: T . coreanum (which has white flowers). Group Ⅱ: T. heterolepis, T. sinomongolicum, T . variegatum, T. asiaticum var . lonchophyllum, T. falcilobum, T. brassicaefolium, and T. erythropodium (outer involucre bracts, narrow membranous or nonmembranous). Group Ⅲ: T . formosanum, T . liaotungense, T . mongolicum, T. borealisinense, T . ohwianum, T. platypecidum, T . urbanum, T. antungense, T . asiaticum, and T. junpeianum (outer involucre bracts, broad membranous). The main taxonomic characteristics of Taraxacum floral organs and achene morphology. Abstract : The study aimed to categorize 18 Taraxacum taxa from northeastern China based on DNA data and cluster analysis of morphological characteristics and test whether the latter supports the molecular‐based phylogeny.